Development of Eco-friendly Self-compacting Concrete Using Fly Ash and Waste Polyethylene Terephthalate Bottle Fiber - Slamet Widodo; Rifki Alfirahma; Alamsyah Prawiranegara; M Fajar Amir; Aniswara Dewi (Civil Engineering Journal, 2023)
This study aims to utilize fly ash and waste PET bottles for producing more sustainable self-compacting concrete (SCC) with better mechanical strength. Fly ash is utilized as a supplementary cement material and waste PET bottles as fiber reinforcement to improve its flexural strength and achieve the targeted compressive strength. The experimental works were conducted on eight variations using 80 specimens, divided into two main groups of partial cement replacement using 0% and 15% fly ash by weight. The two variants are added with PET fiber based on the volume fractions of 0%, 0.25%, 0.50%, and 0.75%. Fresh concrete was tested using the slump flow method (T50) and the Visual Stability Index (VSI) based on ASTM 1611. The hardened concrete tests are conducted after 56 days and include testing the concrete's compressive strength, flexural strength, and ultrasonic pulse velocity. Test results showed that the presence of PET fiber in the SCC mix decreased its flowability. However, when added up to 0.75%, the mixes still meet the flowability requirements of fresh-state SCC. PET fiber addition tends to reduce the compressive strength, whereas the reduction in compressive strength of SCC with PET fiber without fly ash is insignificant. However, in SCC that uses fly ash, the addition of PET fiber causes a significant decrease in its compressive strength. Adding PET fiber into SCC mixes can increase flexural strength, both for the two variants: SCC without fly ash and SCC with fly ash. It can be concluded that PET waste fiber with an aspect ratio of 40 can be added up to 0.5% for SCC without fly ash and up to 0.25% by volume fraction for SCC with fly ash addition. The ultrasonic pulse velocity test results have an excellent tendency to predict the concrete's compressive and flexural strengths. Therefore, the UPV test can be applied for the non-destructive test evaluation of PET fiber-reinforced SCC. Doi: 10.28991/CEJ-2023-09-02-014 Full Text: PDF